Maqasid shariah’s Change as Theory: From Classical to Cotemporary Maqasid Shariah - Wanto, Deri; Hidayat, Rahmad; Repelita, R. (Institut Agama Islam Negeri Curup, 2021)
This article intended to identify the development of maqasid shariah theory and discourse in various published articles from various databases courses. By applying a systematic approach to a literature review, this article identifies the development of themes related to maqasid shariah. This approach is applied to fifty-three article in varied data source like ProQuest, Google Scholars, Scopus database and IRTI-IDB Proceeding. From the maqasid shariah index to maqasid shariah as a legal framework in contemporary fiqh discourse, even fatwa’s by various religious institutions such as the MUI. Nevertheless, the development of maqasid shariah as an analytical framework and paradigm has changed, from a values-based and juridical basis to social indicators.